Karakteristik Kimia Dodol Susu Substitusi Tepung Ketan dengan Tepung Ubi Jalar - Trianing Tyas Kusuma Anggaeni; Andry Pratama (Unpad Press, 2021)
Milk dodol is a dairy product with the main ingredients of milk, glutinous rice flour and coconut milk. Glutinous rice flour can substitute glutinous rice flour using other types of flour. The objectives of this study were to determine the substitution effect of glutinous rice flour with sweet potato flour, and the best ratio in producing of “milk dodol” due to the chemical characteristics. Data were analyzed by using Completely Randomized Design (CRD) with six treatments of substitution, P0 = 100% glutinous rice flour (as control), P1 = 20% sweet potato flour and 80% glutinous rice flour, P2 = 40% sweet potato flour and 60% glutinous rice flour, P3 = 60% sweet potato flour and 40% glutinous rice flour, P4 = 80% sweet potato flour and 20% glutinous rice flour, P5 = 100% sweet potato flour, which was 4 replication. The results showed that the use of sweet potato flour up to 100% still had water content and sugar content that met the quality requirements of dodol based on the Indonesian National Standard.